In-depth genetic diversity and population structure of endangered Peruvian Amazon rosewood germplasm using Genotyping by Sequencing (GBS) technology - Azhar Nadeem, Muhammad; Vasquez Guizado, Stalin Juan; Qasim Shahid, Muhammad; Amjad Nawaz, Muhammad; Habyarimana, Ephrem; Ercişli, Sezai; Ali, Fawad; Karaköy, Tolga; Aasim, Muhammad; Hatipoğlu, Rüştü; Castro Gómez, Juan Carlos; Marapara Del Aguila, Jorge Luis; et al. (MDPI, 2023)
Research studies on conservative genetics of endangered plants are very important to establish the management plans for the conservation of biodiversity. Rosewood is an evergreen tree of the Amazon region and its essential oil has great acceptance in the medical and cosmetic industry. The present study aimed to explore the genetic diversity and population structure of 90 rosewood accessions collected from eight localities of Peruvian Amazon territory through DArTseq markers. A total of 7485 informative markers resulted from genotyping by sequencing (GBS) analysis were used for the molecular characterization of rosewood germplasm. Mean values of various calculated diversity parameters like observed number of alleles (1.962), the effective number of alleles (1.669), unbiased expected heterozygosity (0.411), and percent polymorphism (93.51%) over the entire germplasm showed the existence of a good level of genetic variations. Our results showed that the Mairiricay population was more diverse compared to the rest of the populations. Tamshiyacu-2 and Mairiricay-15 accessions were found genetically distinct accessions. The analysis of molecular variance (AMOVA) reflected maximum variations (75%) are due to differences within populations. The implemented clustering algorithms, i.e.; STRUCTURE, neighbor-joining analysis and principal coordinate analysis (PCoA) separated the studied germplasm on the basis of their geographical locations. Diversity indices for STRUCTURE-based populations showed that subpopulation A is more diverse population than the rest of the populations, for such reason, individuals belonging to this subpopulation should be used for reintroduction or reinforcement plans of rosewood conservation. We envisage that molecular characterization of Peruvian rosewood germplasm with DArTseq markers will provide a platform for the conservation, management and restoration of endangered rosewood in upcoming years.